Investigating the social world : the process and practice of research - Schutt, Russell K. (Los Angeles, Calif. : SAGE Publications, 2012)
'A comprehensive, balanced text text for Research Methods courses found in Sociology, Communication/Journalism, Political Science, Public Administration, and other social science disciplines. It is used in undergraduate through graduate level courses'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Social problems -- Research; Social sciences -- Research